In vitro replication of tobacco mosaic virus RNA in tobacco callus cultures: solubilization of membrane-bound replicase and partial purification. - White, J L (1977)
A fraction containing membrane-bound tobacco mosaic virus RNA replicase was isolated form tobacco mosaic virus-infected tobacco callus cultures. The replicase activity reached a maximum 60 h after inoculation and then declined. The enzyme activity was insensitive to actinomycin D and DNase. The corresponding fraction from healthy callus contained essentially no activity. The viral RNA synthesis in vitro proceeded linearly for 30 min and required the four nucleotide triphosphates and Mg2+ ions. Mn2+ was a poor substitute for Mg2+. During RNA synthesis the product was at least 70% resistant to RNase in 2X SSC (0.15 M NaCl plus 0.015 M sodium citrate), but completely digested by RNase in 0.1X SSC. Analysis of the product by polns) that appeared to be replicative form and a partially RNase-resistant structure similar to replicative intermediate form. Washing the membrane-bound replicase with Mg2+-deficient buffer solubilized enzyme. The solubulized enzyme was further purified by DEAE-Sephadex column chromatography. The DEAE-purified enzyme was nearly completely dependent upon tobacco mosaic virus RNA for activity. Analysis of the product on a sucrose gradient revealed a double-stranded RNA with sedimentation of 16S and smaller heterogeneous RNase-sensitive products.